2023
DOI: 10.55188/ijif.v15i1.488
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Performance of Islamic Banks in the MENA Region

Abstract: Purpose — This research explores the impact of COVID-19 on the financial return of Islamic banks (IBs) in nine countries located in the Middle East and North Africa (MENA) region. It also examines the determinants of IBs’ profitability during stable and uncertain periods, namely before and during the development of coronavirus. Design/Methodology/Approach — The financial data of this paper were collected from annual reports of IBs and the Orbis Bank Focus database over four years: 2018, 2019, 2020 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…For Lloyd (2009), the non-performing corporate governance mechanisms in US banks caused the financial crisis of 2008. EL-Chaarani (2014, 2015 confirmed the importance of corporate governance mechanisms as determinants factors of the performance of the banking sector. In the same line, Brogi and Lagasio (2022) indicated that a bad governance structure leads to destroy the stability and soundness of the banking sector.…”
Section: Introductionmentioning
confidence: 67%
“…For Lloyd (2009), the non-performing corporate governance mechanisms in US banks caused the financial crisis of 2008. EL-Chaarani (2014, 2015 confirmed the importance of corporate governance mechanisms as determinants factors of the performance of the banking sector. In the same line, Brogi and Lagasio (2022) indicated that a bad governance structure leads to destroy the stability and soundness of the banking sector.…”
Section: Introductionmentioning
confidence: 67%
“…The more capital the bank has, the larger loan exposure and other expansion can be achieved, while variable NIM contributes to the profit from the interest income of the loan exposure. The macroeconomic variable of GDP growth describes the growth of the economy and financial system, which influence the financial transactions through the banking industry and contribute to bank profitability [66,[71][72][73][74][75][76].…”
Section: Panel Ardl Estimationmentioning
confidence: 99%